A multi-objective approach to integrate solar and wind energy sources with electrical distribution network. (February 2015) - Kayal, Partha; Chanda, C.K.
Highlights: Novel techno-economic optimization for grid connected solar–wind system. Uncertainty modeling of solar and wind power generation and its validation. Analyses the impacts of renewable energies considering demand side management. Prominent role of power factor in renewable energy system design. Abstract: Solar and wind energies are the need of the hour worldwide and their high penetration in electricity power grid cause sensible amount of problems (stick to the grid code of respective country) due to randomness and uncertain generation pattern. Therefore reinforcement of intermittent renewable energy sources requires due attention to achieve optimum economical as well as operational benefit. This paper presents a novel techno-economic optimization method for proper location and size selection of multiple solar and wind generation units in distribution network. Multi-objective particle swarm optimization technique (MOPSO) is adopted to generate potential solutions by trade-off between payback year, reduction of power loss and voltage stability level of the network. The strategic planning method has been tested on a typical Indian rural distribution network. It is shown that the proposed method offers the workable solution to get the desired result.